UNIFIED APPROACH TO THE INTERPRETATION OF COMPETENCE IN SOCIAL MANAGEMENT AND EDUCATION - Andrew N. Pechnikov (Образование и наука)
RETRACTED ARTICLEThe aim of the publication – a description of the approach to theinterpretation of the concept of competence, adequately implements the interaction of social control and education.Methods. The methods of analysis and synthesis are used.Results and scientific novelty. The content of the concept of «competence» in personnel management is disclosed. Counterefficiency of interpretations of concept of competence of subject domain of pedagogics and expediency of acceptance of the definitions formulated in the sphere of social management (personnel management) are proved.Practical significance consists in justification of an approach to the interpretation of competences, which adequately reflects the patterns of interaction of social control and education.